2021
DOI: 10.1021/jacs.1c09665
|View full text |Cite
|
Sign up to set email alerts
|

Intermetallic Nanocatalyst for Highly Active Heterogeneous Hydroformylation

Abstract: Hydroformylation is an imperative chemical process traditionally catalyzed by homogeneous catalysts. Designing a heterogeneous catalyst with high activity and selectivity in hydroformylation is challenging but essential to allow the convenient separation and recycling of precious catalysts. Here, we report the development of an outstanding catalyst for efficient heterogeneous hydroformylation, RhZn intermetallic nanoparticles. In the hydroformylation of styrene, it shows three times higher turnover frequency (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 32 publications
0
30
0
Order By: Relevance
“…With the increase of temperature, CO that adsorbed on the surface of the catalysts gradually desorbed, in which Ni 1 Mo 2 /Al 2 O 3 -IM completely desorbed at 60 °C and Al 2 O 3 @Ni 1 Mo 2 -LDO completely desorbed at 180 °C. A temperature-programmed desorption study using DRIFTS further revealed that the CO peaks shifted to a lower wavenumber with an increase in temperature on the metal surface, indicating that CO dipole–dipole coupling was eliminated with the decrease of CO coverage . It can be concluded that the core–shell catalyst was more capable of adsorption of CO, which can enable the ability to increase binding to the active site.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…With the increase of temperature, CO that adsorbed on the surface of the catalysts gradually desorbed, in which Ni 1 Mo 2 /Al 2 O 3 -IM completely desorbed at 60 °C and Al 2 O 3 @Ni 1 Mo 2 -LDO completely desorbed at 180 °C. A temperature-programmed desorption study using DRIFTS further revealed that the CO peaks shifted to a lower wavenumber with an increase in temperature on the metal surface, indicating that CO dipole–dipole coupling was eliminated with the decrease of CO coverage . It can be concluded that the core–shell catalyst was more capable of adsorption of CO, which can enable the ability to increase binding to the active site.…”
Section: Resultsmentioning
confidence: 98%
“…In addition, it was found that the chemical state of Ni species in Al to a lower wavenumber with an increase in temperature on the metal surface, indicating that CO dipole−dipole coupling was eliminated with the decrease of CO coverage. 37 It can be concluded that the core−shell catalyst was more capable of adsorption of CO, which can enable the ability to increase binding to the active site. It was favorable for the deoxygenation reaction of oxygen-containing compounds.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The Supporting Information is available free of charge at https://pubs.acs.org/doi/10.1021/acssuschemeng.2c04674. More details about the experiments, including characterization conditions of m-3vPAr 3 -POLs and corresponding supported catalysts; 1 H, 13 C, and 31…”
Section: ■ Conclusionmentioning
confidence: 99%
“…For example, Zhang’s group prepared a series of Rh/ZnO-nw catalysts employing the strong metal–support interaction (SMSI) between ZnO and Rh species, and the afforded catalysts exhibited good activity in the hydroformylation of styrene . Huang’s group used Zn species and Rh species to synthesize the intermetallic compounds and loaded them on SBA-15 to prepare an efficient hydroformylation catalyst, which exhibited 3 times more activity than the homogeneous Wilkinson catalyst in the hydroformylation of styrene . However, Rh–P complex catalysts are still the best choice for heterogeneous hydroformylation reactions due to their superior catalytic performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation